PENELITIAN KARAKTERISTIK AERODINAMIKA AEROFOIL SUDU SKEA NELAYAN NILA 80 - Sulistyo Atmadi (National Institute of Aeronautics and Space - LAPAN, 2004)
An economical electric-small-scale wind turbine is intended for an alternative source of energy for fishermans. For the power requirment of wind turbine with the wind condition in Indonesia, an aerofoil research is needed, in particular for the case of SKEA Nelayan Nila 80, with unknown aerofoil data. The focus of the research concentrated on finding aerodynamics characteristic Cl, Cd and Cm for angle of attack regime from 4 to 16 degrees. The result would be used in the modification of existing wind turbine. With limited engineering data, several integrated softwares had been used such as AutoCad 2004, Gambit and fluent 5.2.1 AutoCad was used to digitise aerofoil geometry, gambit was used for grid generation wich then fed into Fluent 5.2.1. for load analysis. The result was quite similiar to N-60 which gives stall angle at around 13 degree-15 degree and Cl per Cd maximum equal 16.